1999
DOI: 10.1523/jneurosci.19-07-02619.1999
|View full text |Cite
|
Sign up to set email alerts
|

Topographic Organization of Human Visual Areas in the Absence of Input from Primary Cortex

Abstract: Recently, there has been evidence for considerable plasticity in primary sensory areas of adult cortex. In this study, we asked to what extent topographical maps in human extrastriate areas reorganize after damage to a portion of primary visual (striate) cortex, V1. Functional magnetic resonance imaging signals were measured in a subject (G.Y.) with a large calcarine lesion that includes most of primary visual cortex but spares the foveal representation. When foveal stimulation was present, intact cortex in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 53 publications
9
108
1
Order By: Relevance
“…The study involved patient GY, a patient with blindness in his right visual field following a lesion to his left V1 and well-documented blindsight (for a detailed description of the patient see : Baseler, Morland, & Wandell, 1999;Bridge, Thomas, Jbabdi, & Cowey, 2008;Goebel, Muckli, Zanella, Singer, & Stoerig, 2001;. In May 1997 GY came to our lab in Tilburg, accompanied by Larry Weiskrantz, to give us the opportunity to test some of Paul Bertelson's ideas about the automaticity of ventriloquism and to participate in ongoing studies on the role of visual awareness in audiovisual speech perception.…”
Section: The Originsmentioning
confidence: 99%
“…The study involved patient GY, a patient with blindness in his right visual field following a lesion to his left V1 and well-documented blindsight (for a detailed description of the patient see : Baseler, Morland, & Wandell, 1999;Bridge, Thomas, Jbabdi, & Cowey, 2008;Goebel, Muckli, Zanella, Singer, & Stoerig, 2001;. In May 1997 GY came to our lab in Tilburg, accompanied by Larry Weiskrantz, to give us the opportunity to test some of Paul Bertelson's ideas about the automaticity of ventriloquism and to participate in ongoing studies on the role of visual awareness in audiovisual speech perception.…”
Section: The Originsmentioning
confidence: 99%
“…There are positron emission tomographic, electroencephalographic, and magnetoencephalography data that suggest that the MTϩ/V5 region of visual cortex can be activated by moving stimuli in a well studied patient (G.Y.) with a loss of much of V1 (Barbur et al, 1993;ffytche et al, 1996), yet a more recent functional magnetic resonance imaging (fMRI) study in the same patient (Baseler et al, 1999) showed no activation in MTϩ/V5, and the authors suggested that the visual behavior in blindsight may depend on callosal inputs from the intact hemisphere. In addition, there is evidence from other patients with V1 lesions that small islands of V1 are often preserved, and that the effectiveness of visual detection depends on these islands of V1 and possibly on their projections to MT (Fendrich et al, 2001).…”
Section: The Role Of Mt In Blindsightmentioning
confidence: 99%
“…In addition, there is evidence from other patients with V1 lesions that small islands of V1 are often preserved, and that the effectiveness of visual detection depends on these islands of V1 and possibly on their projections to MT (Fendrich et al, 2001). Evidence from fMRI indicates that small, preserved portions of V1 in humans are capable of activating largerthan-normal portions of extrastriate cortex, and that callosal inputs also expand their territories of activation (Baseler et al, 1999).…”
Section: The Role Of Mt In Blindsightmentioning
confidence: 99%
“…Subject GY has been studied extensively over the past 20 years (Barbur et al 1980(Barbur et al , 1993Baseler et al 1999;Cowey & Stoerig 2004). Following a car accident at the age of 8 years, GY suffered an extensive lesion in the region of the left primary visual cortex (figure 6a) and in the right parietal lobe (not shown).…”
Section: Application Of the Methodology To Abnormal Brainsmentioning
confidence: 99%
“…The spared region of V1 corresponding to central vision can be seen on a normal MRI scan of the brain, as it is clear that the damage did not extend all the way to the back of the brain. Baseler et al (1999) used fMRI to produce a retinotopic map for patient GY in both his affected and unaffected hemispheres. While the retinotopic map showed activation in the spared central region of the visual field, activity in the dorsal part of primary visual cortex, which would correspond to the strip in the lower visual field, was not obvious.…”
Section: Application Of the Methodology To Abnormal Brainsmentioning
confidence: 99%